2015
DOI: 10.1371/journal.ppat.1004621
|View full text |Cite
|
Sign up to set email alerts
|

A Specific A/T Polymorphism in Western Tyrosine Phosphorylation B-Motifs Regulates Helicobacter pylori CagA Epithelial Cell Interactions

Abstract: Helicobacter pylori persistently colonizes the human stomach, with mixed roles in human health. The CagA protein, a key host-interaction factor, is translocated by a type IV secretion system into host epithelial cells, where its EPIYA tyrosine phosphorylation motifs (TPMs) are recognized by host cell kinases, leading to multiple host cell signaling cascades. The CagA TPMs have been described as type A, B, C or D, each with a specific conserved amino acid sequence surrounding EPIYA. Database searching revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 85 publications
5
75
1
3
Order By: Relevance
“…Tyrosine phosphorylation of EPIYA/T B-TPMs were reported to be involved in the regulation of host cell signaling cascades and interacted with epithelial cells [30]. In this study, most strains possessed EPIYA, not EPIYT B-TPMs, which were in agreement with the previous report that most East Asian strains (91.1%) possessed EPIYA B-TPMs [30].
Fig.
…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tyrosine phosphorylation of EPIYA/T B-TPMs were reported to be involved in the regulation of host cell signaling cascades and interacted with epithelial cells [30]. In this study, most strains possessed EPIYA, not EPIYT B-TPMs, which were in agreement with the previous report that most East Asian strains (91.1%) possessed EPIYA B-TPMs [30].
Fig.
…”
Section: Discussionsupporting
confidence: 92%
“…Recent data revealed a strong non-random distribution of the B-motifs (including EPIYA and EPIYT) in CagAs. The EPIYT B-tyrosine phosphorylation motifs (TPMs) were significantly less associated with GC than the EPIYA B-TPMs [30]. In this study, most strains possessed EPIYA B-TPMs, except for three strains with ESIYA or ESIYT B-TPMs (one strain from GC had ESIYA B-TPM, and one strain from gastritis and one strain from MALT lymphoma had ESIYT B-TPM).…”
Section: Resultsmentioning
confidence: 75%
“…The number and types of repeats have been associated with differing risks of carcinogenesis 58 . Recently, it was reported that the EPIYA-B motif binds and activates PI3-kinase and AKT, but many Western strains of H pylori carry a single nucleotide polymorphism in this domain that reduces its association with PI3 kinase and also reduces the risk of gastric cancer 59 . The amount of CagA and its cellular target are also likely to have important roles in pathogenesis, but little is known about the precise location and timing CagA delivery.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…The type and number of CM motifs may influence the potential for individual CagA proteins to multimerize in host cells, and this may affect the ability of CagA to disturb host cell function via SHP-2 deregulation [33]. The EPIYT is the second most common EPIYA-B motif in Western-type cagA , but is very rarely observed in East-Asian-type- cagA [34]. Zhang et al .…”
Section: Association Between H Pylori Virulence Genes and Pudmentioning
confidence: 99%
“…Zhang et al . analyzed 364 Western-type- cagA and reported that gastric cancer is more significantly associated with EPIYA sequences in the EPIYA-B motif compared with gastritis alone, whereas EPIYT sequences are significantly associated with DU [34]. …”
Section: Association Between H Pylori Virulence Genes and Pudmentioning
confidence: 99%